Do Elections Influence Abnormal Stock Returns? Comparative Evidence Across General Elections in Malaysia - Racquel, Rowland; Venus Khim Sen, Liew (HRMARS, 2025)
The study examines the impact of election on market index in the context of Malaysia by analyzing the magnitude of market reaction in different election years towards political transition to see whether it is more intensify as compared to one-party administration. This study employs market model event study over a sample period covering seven general elections (GE9 – GE15), from 1995 to 2022. The findings indicate that election has significant impact on the abnormal return (AR) and cumulative abnormal return (CAR) of FBMKLCI, albeit mixed results in certain windows during GE12 to GE14. This implies Malaysia equity market exhibits semi-strong form of market efficiency as electoral outcomes are rapidly incorporated into stock prices within a short time frame especially during windows [-5,5], despite the occurrence of electoral shocks during those periods.